Strategi Orang Tua Untuk Mencegah Kenakalan Remaja Pada Anak: Pendekatan Pola Asuh Dan Pendidikan Karakter - Muti’ah, Muti’ah; Marlina, Marlina; Iriyani, Sri Astuti; Rahim, Abdul; Irhas, Irhas (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2023)
Character education plays a significant role in shaping the personality of individuals, especially the younger generation in facing the challenges of modern society. Parents play a major role in teaching moral and ethical values to children. This community service aims to increase the role of parents in character education to minimize juvenile delinquency. Through a socialization approach, this activity was carried out in Salut Kendal Hamlet, North Lombok Regency with the cooperation of the NGO Yayasan Seleksa Sejahtera Mataram. From this community service activity, it is hoped that parents can play a greater role in strengthening character education in children to prevent juvenile delinquency. An understanding of character education and the role of parents is essential in making good decisions, especially in educating children holistically.